An Analysis of the Management of the 'Tasbih' Hajj Savings Product at Bank Sumsel Babel Based on the Wadi’ah Principle in the Perspective of DSN-MUI Fatwa No. 02/DSN-MUI/IV/2000 - Rafika Aulia; Meydiah Astuti; Nova Rahmadaniarti (CV. Era Digital Nusantara, 2025)
Hajj savings is a Sharia-compliant financial product designed to facilitate Muslims in preparing for and financing the pilgrimage to Mecca. This product allows customers to open a special savings account, make an initial deposit, and settle the Hajj Travel Cost (BPIH). The funds in this account are not withdrawable at any time, but are subject to specific regulations. This study aims to analyze the management of the